Adherence to Iron-Folic Acid Supplementation and Associated Factors among Pregnant Women in Kasulu Communities in North-Western Tanzania - Lyoba, Winfrida B.; Mwakatoga, Joyce D.; Festo, Charles; Mrema, Jackline; Elisaria, Ester (International Journal of Reproductive Medicine, 2020)
Introduction. Pregnant women are at a high risk of anaemia, with iron-folate deficiency being the most common cause of anaemia among pregnant women. Despite the well-known importance of iron and folic acid supplementation (IFAS) during pregnancy, adherence to these supplements is relatively low and associated factors were not well identified in the study area. This study is aimed at investigating adherence to IFAS and associated factors among pregnant women in Kasulu district, north-western Tanzania. Methods. A health facility cross-sectional survey with a mixed-method approach was conducted in Kasulu district from March to April 2019. A structured questionnaire was given to 320 women with children aged 0-6 months to assess factors associated with adherence to IFAS among pregnant women. Data were entered into SPSS version 22.0 for analysis. Binary logistic regression was further employed to determine the factors associated with adherence to IFAS. Focus group discussions were done with 19 pregnant women and 15 mothers of children aged 0-6 months to obtain more clarifications on the factors associated with adherence to IFAS. Furthermore, in-depth interviews were done with six health care providers to explore their perceptions of IFAS. Results. Out of the 320 respondents of the survey, 20.3% (n=65) adhered to IFAS. Factors associated with adherence to IFAS among pregnant women included time to start ANC (AOR=3.72, 95% CI: 1.42, 9.79), knowledge of anaemia (AOR=3.84, 95% CI: 1.335, 10.66), counseling on the importance of the iron-folic acid (AOR=3.86, 95% CI: 1.42, 10.50), IFAS given during clinical visit (AOR=15.72, 95% CI: 5.34, 46.31), number of meals consumed (AOR=3.44, 95% CI: 1.28, 9.21), number of children (AOR=3.462, 95% CI: 1.035, 11.58), and distance to health facility (AOR=0.34, 95% CI: 0.131, 0.886). Qualitative findings revealed that delayed first ANC visit, lack of remainder for pregnant women to take IFAS, low awareness about the negative effects of anaemia, low of knowledge of IFAS and management of side effects, negative beliefs about the use of IFAS, and follow-up mechanism were major reasons for poor adherence. Conclusion. Adherence to iron-folic acid supplementation during pregnancy was low. Strengthening systems for creating reminding mechanism, raising community awareness through educational programs to pregnant women and health providers could improve adherence to IFAS.